HLA-A*23 Is Associated With Lower Odds of Acute Retroviral Syndrome in Human Immunodeficiency Virus Type 1 Infection: A Multicenter Sub-Saharan African Study - Lindquist, L; Kilembe, W; Karita, E; Price, MA; Kamali, A; Kaleebu, P; Tang, J; Allen, S; Hunter, E; Gilmour, J; Rowland-Jones, SL; Sanders, EJ; et al. (Oxford University Press, 2024)
The role of human leukocyte antigen (HLA) class I and killer immunoglobulin-like receptor molecules in mediating acute retroviral syndrome (ARS) during human immunodeficiency virus type 1 (HIV-1) infection is unclear. Among 72 sub-Saharan African adults, HLA-A*23 was associated with lower odds of ARS (adjusted odds ratio, 0.10 [95% confidence interval, .01–.48]; P = .009), which warrants further studies to explore its role on HIV-1–specific immunopathogenesis.